Agave and Yucca: Tough Plants for Tough Times - Gary W. Knox (EDIS, 2010)
ENH1159, an 18-page illustrated fact sheet by Gary W. Knox, describes these tough, low-maintenance plants that thrive in the sometimes harsh conditions associated with urban environments — requirements and placement, water and fertilizer, pests, diseases, and cultural problems, container gardening, propagation, historical and modern uses, and agave toxicities. Includes references. Published by the UF Department of Environmental Horticulture, February 2010.